THE INFLUENCE OF PROFESSIONAL COMPETENCE OF TEACHER SD ON STUDENT LEARNING OUTCOMES - syifa Muhafillah (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2018)
Student learning outcomes can be influenced by a teacher, because teachers can direct and guide students in achieving learning success. Teacher professional competence is a set of abilities a teacher must possess in order for him to carry out his teaching task successfully. This study aims to determine the effect of professional competence of elementary school teachers on student learning outcomes. The type of research used is quantitative research based on regression analysis. The subjects of this study were 15 teachers and 6th graders, 36 students at SDN Leuwiliang 01, and 15 teachers and grade VI students who were 34 in SDN Leuwiliang 04 Leuwiliang District. The data were summarized using obsevation, questionnaires and interviews. The result of this research is the data of filling questionnaires from 30 gur and 70 students using t test obtained t count = 2.275>ttable = 1.990 so that the influence of professional competence of Sd teacher toward student learning result is significant. Form of regression equation Y = 43.296 = 0.438X. This research has effective contribution of R2 = 0.296, which shows 29.6% variable of student learning result influenced by teacher professional competence, the rest 7.4% influenced by other factor not analyzed in this research. Thus, the higher the professional competence of teachers, the more student learning outcomes in SDN Leuwiliang 01 and in SDN Leuwiliang 04 Leuwiliang District Bogor Regency